Feasibility of individualized home exercise programs for patients with head and neck cancer-study protocol and first results of a multicentre single-arm intervention trial (OSHO #94). - Sabine Felser; Julia Rogahn; Änne Glass; Lars Arne Bonke; Daniel Fabian Strüder; Jana Stolle; Susann Schulze; Markus Blaurock; Ursula Kriesen; Christian Junghanss; Christina Grosse-Thie (PLoS ONE)
Introduction Patients with head and neck cancer (PwHNC) benefit from targeted exercise interventions: symptom relief, compensation for dysfunction, improvement in quality of life (QoL). Data on acceptance physical interventions in PwHNC are rare. The 'OSHO #94' trial investigates the short- and medium-term effects of individualized home exercise in PwHNC on QoL, physical activity and functionality. The study includes a feasibility phase (proof of concept) in order to evaluate the acceptance. Here we present the study protocol as well as the feasibility results. Methods and analysis This prospective, multicentre, single-arm intervention study includes PwHNC ≥18 years of age in aftercare or palliative care with stable remission under immunotherapy. The study opened in January 01, 2021, with estimated completion by December 31, 2024. The PwHNC receive an individualized home exercise program consisting of mobilization, coordination, strengthening and stretching exercises. This should be carried out at least three times a week over 12 weeks for 15 to 30 minutes, supplemented by aerobic training two to three times a week for 30 minutes (intervention). Once weekly telephone calls with a physiotherapist are performed. Subsequently, there is a 12-week follow-up (FU) without exercise specifications/contact. Outcomes are measured before and after the intervention and following the FU. Primary outcome of the feasibility phase (n = 25) was the determination of the dropout rate during the intervention with a termination cut off if more than 30% PwHNC withdrew premature. The primary outcome of the OSHO #94' trial (N = 53) is the change in global QoL score from pre- to post-intervention (EORTC QLQ-C30). Secondary outcomes include clinical and patient-reported measures, training details as well as functional diagnostic data (e.g. level of physical activity, training frequency, flexibility, fall risk and aerobic performance). Results 25 PwHNC were enrolled onto the feasibility cohort. Only16% (4/25 patients) did not complete the study. Therefore, recruitment of PwHNC was continued. The dropout rate was adjusted from 30% (N = 60) to 20% (N = 53, calculated sample size n = 42 PwHNC and 20% (n = 11) to dropout). Conclusions Individualized home exercise programs in PwHNC in aftercare seem feasible. Consequently, the aim is now to evaluate the short and medium-term effects of individualized home exercise.